2010
DOI: 10.1007/s00216-010-3726-4
|View full text |Cite
|
Sign up to set email alerts
|

Capillary electrophoresis frontal analysis for the study of flavonoid interactions with human serum albumin

Abstract: Capillary electrophoresis based on the principles of frontal analysis (CE-FA) was used to characterize the binding of flavonoids to human serum albumin (HSA) at near-physiological conditions: 67 mM phosphate buffer (pH 7.4), temperature 36.5 degrees C. The studied flavonoids (flavone, rutin, quercitrin) displayed moderate affinities toward the human serum albumin with binding constants in the range 10(3)-10(4) M(-1). The binding of the flavonoids to the protein noticeably depended on their lipophilicity and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…A variety of techniques were reported for the study of protein and phenolic compound interaction, such as equilibrium dialysis, 1,2 ultrafiltration, 3,4 fluorescence spectroscopy, 5 capillary electrophoresis, 6 and isothermal titration calorimetry (ITC). 4,7 Although most techniques are used to probe the kinetic and equilibrium parameters, the ITC method is used to determine the thermodynamic properties as well as equilibrium parameters of protein-ligand interactions.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of techniques were reported for the study of protein and phenolic compound interaction, such as equilibrium dialysis, 1,2 ultrafiltration, 3,4 fluorescence spectroscopy, 5 capillary electrophoresis, 6 and isothermal titration calorimetry (ITC). 4,7 Although most techniques are used to probe the kinetic and equilibrium parameters, the ITC method is used to determine the thermodynamic properties as well as equilibrium parameters of protein-ligand interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The displacement studies were performed by using several methods, including ultrafiltration [10], ED [11], crystallographic studies [12], CD [13], fluorescence spectroscopy [14, 15], molecular modeling [16], high‐performance affinity chromatography [17], and capillary electrophoresis (CE) in different modes including affinity CE, vacancy affinity CE, partial filling CE, near‐infrared dye‐displacement CE or CE‐FA [1, 1821]. Despite the fact that CE‐FA method is widely used for binding parameters determination only a few research groups reported about its applicability for displacement studies [22–29]. CE‐FA method was chosen for these measurements in view of its many benefits, which include small sample consumption, robustness and the possibility of high‐throughput screening [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Noncovalent interaction includes electrostatic interaction, van der Waals interaction, hydrogen bonds, hydrophobic interaction, and π bonds. Noncovalent interaction between protein and phenolic compounds can be studied by various techniques such as equilibrium dialysis (ED), , ultrafiltration, , ultraviolet–visible absorption spectroscopy (UV–vis), , fluorescence spectroscopy, , capillary electrophoresis, and isothermal titration microcalorimetry (ITC). ,, Using ED and ultrafiltration, the thermodynamic equilibrium of phenolic compounds binding to protein can be determined. However, phenolic compounds can also bind to the membrane used.…”
Section: Introductionmentioning
confidence: 99%